O discurso construtivista como norteador da qualidade do processo de ensino e aprendizagem - Santos, Ana Maria dos (2008)
The current paper analyzes the constructivist discourse as the guideline on quality of the learning and teaching process. We start from the acknowledgement that constructivism has not arisen in educational view as a secondary element, but as central factor in educational policies implemented in the 1990s. The constructivist ideary is seen as impregnated with a negative perspective of teaching work, once it is shown as a novelty in education by resuming the principles of Escola Nova , which focuses learning and teaching process on the learner and the teacher is a mere mediator in this process. The theoretical and methodological foundation of this investigation is the Discourse Analysis of French trend, whose core concepts are the ideology and discourse. In this viewpoint, discourse is seen as process, as movement of meanings, which dialogues with other discourses. The linguistic materiality of our corpus is constituted by some discursive sequences taken from printed material devised for continuous formation of teachers in Brazil PROFA and Pró-Letramento through partnership between the Ministry of Education and town halls. From our analysis, we conclude that the official discourse insists on establishing a close relation between the constructivist practice and the quality education, thus using seduction and alienating strategies.